Fourier-Transform IR spectroscopic investigations of Cobalt(II)–dextran complexes by using D2O isotopic exchange. Issue 3 (2010) - Mitic, Žarko; Cakic, Milorad; Nikolic, Goran
Abstract : Co(II) ion complexes with reduced low-molar dextran (RLMD) derivatives M w = 5000 − 6000 g/mol, their FTIR spectroscopic characterization, as well as the spectra-structure correlation was investigated in this work. The samples of Co(II) ion complexes with RLMD were deuterated (D2 O, Merck) for 2 h, at room temperature, in vacuum. FTIR spectra as an average of 40 scans were recorded at room temperature in the range 4000 – 400 cm −1 . FTIR investigation of Co(II)–RLMD complexes by D2 O isotopic exchange proved to be a very sensitive method for determining OH group coordination and is related to the hydrogen bond strength. The results of our investigation point to the dextran and their complexes with Co(II) ion are crystalline hydrate molecules. The correlation of physicochemical, spectrophotometric and spectroscopic investigations of these complexes, coordination chemistry of Co(II) ion and the structure of an exopolysaccharide chain are proposed different model structures of the synthesized Co(II) complexes.